KAJIAN KEPATUHAN WAJIB PAJAK PRIBADI DITINJAU DARI PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PERPAJAKAN - Sukma Ayu Fardha Jihin; Wiwit Apit Sulistyowati; Salta (Faculty of Economics and Business, Universitas Warmadewa, 2021)
Each taxpayer must comply with the general provisions of taxation that already exist, but the taxpayer cannot be separated from his negligence in fulfilling tax obligations, for that tax compliance is an attempt by a taxpayer in fulfilling and implementing the tax liability is in accordance with the rules in the tax laws. Therefore this study aims to analyze and determine the effect of understanding tax regulations and tax sanctions on the compliance of individual taxpayers who are registered at KPP Pratama Cirebon Satu. The sample used in this study were 100 personal taxpayers. This type of research is basic research. The primary data collection method used is a survey method using questionnaire media. Data analysis method used is multiple regression analysis using SPSS software version 25. The results of this study indicate that the understanding of tax regulations and tax penalties affect the personal taxpayers compliance registered at KPP Pratama Cirebon Satu.